Predictive Factors for Clinical Outcomes after Primary Descemet's Membrane Endothelial Keratoplasty for Fuchs' Endothelial Dystrophy. (1st February 2019) - Brockmann, Tobias; Pilger, Daniel; Brockmann, Claudia; Maier, Anna-Karina B.; Bertelmann, Eckart; Torun, Necip
ABSTRACT: Purpose : The purpose of this study is to identify predictors for the best-corrected visual acuity (BCVA), central corneal thickness (CCT), and the endothelial cell density (ECD) after primary Descemet's membrane endothelial keratoplasty (DMEK). Methods : In a prospective observational study, 108 eyes with Fuchs' endothelial dystrophy underwent a primary DMEK. Preoperative data, histologic parameters from host's Descemet's membrane, and follow-up data of the first eye were analyzed in regard to BCVA, CCT, and ECD, 12 months after surgery. Results : Overall, 12 months postoperative, the BCVA improved to 0.11 ± 0.11 logMAR, the CCT declined to 529 ± 42 µm, and the ECD measured 1675 ± 418 cells/mm 2 . A significant influence of the preoperative CCT on postoperative BCVAs and CCTs was observed ( r  = 0.299, p  = 0.014 and r  = 0.507, p  < 0.001, respectively). Especially eyes with a CCT <625 µm demonstrated a better BCVA (0.05 ± 0.07 logMAR) than eyes with a CCT ≥625 µm (0.13 ± 0.11 logMAR, p  = 0.002). Furthermore, the identification of eyes with an early visual restitution was possible by considering follow-up data of the first eye. A preoperative CCT ≥625 µm was also sensitive to identify eyes with a persistent corneal swelling. The anterior banded layer thickness, which was obtained histologically, correlated to the preoperative CCT and the frequency of graft detachments ( r  = 0.601, p  = 0.023 and r  = 0.652, p  = 0.041, respectively). Furthermore, a graft's baseline ECD ≤2100 cells/mm 2 was found to be a risk factor for an ECD deterioration under 1000 cells/mm 2 ( 1.8% vs. 15.8%, p  = 0.020). Conclusions : Simple clinical parameters, such as the preoperative CCT, the course of visual restitution of the first eye, and the graft's baseline ECD, are efficient predictors for relevant outcome parameters after DMEK and therefore may be used for stratification. Furthermore, our findings indicate that a DMEK should be performed in eyes with Fuchs' endothelial corneal dystrophy, if possible, before the CCT exceeds 625 µm to maintain good clinical results.